3x-9=4x-24

Simple and best practice solution for 3x-9=4x-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-9=4x-24 equation:


Simplifying
3x + -9 = 4x + -24

Reorder the terms:
-9 + 3x = 4x + -24

Reorder the terms:
-9 + 3x = -24 + 4x

Solving
-9 + 3x = -24 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-9 + 3x + -4x = -24 + 4x + -4x

Combine like terms: 3x + -4x = -1x
-9 + -1x = -24 + 4x + -4x

Combine like terms: 4x + -4x = 0
-9 + -1x = -24 + 0
-9 + -1x = -24

Add '9' to each side of the equation.
-9 + 9 + -1x = -24 + 9

Combine like terms: -9 + 9 = 0
0 + -1x = -24 + 9
-1x = -24 + 9

Combine like terms: -24 + 9 = -15
-1x = -15

Divide each side by '-1'.
x = 15

Simplifying
x = 15

See similar equations:

| 3(4x+1)=3+12x-3 | | 36+2y-15=12y-9-5y | | 8-4+2R-4R+8R= | | 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 | | 24b+4=52 | | (x-3)(x-4)-(x+4)=0 | | 2n^3-24n^2-23048n=0 | | 4.3+7.5=5.8 | | 10v^2=11v+6 | | -3-10=-46 | | -(12+2r)-(r+8)=-7r+3r | | 10U-2U= | | 6x^2-13x+4= | | 4.29b-0.692=11.749 | | 3[2(5x-7)-3(4x-6)]-4[5(x-1)-7x]=6[-4(x+2)+7x] | | 6+5(8w-9)= | | 36=2L+W | | 1w+5=4 | | 3-2(x-4)=2x-5 | | 3(4x+1)=3+12x-2 | | (X+10)+(4x-20)=90 | | 7R*2+8R+8R= | | 3x(.29)=3 | | 1y+-4x= | | 8v-18=26+3v | | 18+4(-4)= | | 50-40x=200 | | 3t-t=20 |

Equations solver categories